Biomechanical relationships between the corneal endothelium and Descemet's membrane. (November 2016) - Ali, Maryam; Raghunathan, VijayKrishna; Li, Jennifer Y.; Murphy, Christopher J.; Thomasy, Sara M.
Abstract: The posterior face of the cornea consists of the corneal endothelium, a monolayer of cuboidal cells that secrete and attach to Descemet's membrane, an exaggerated basement membrane. Dysfunction of the endothelium compromises the barrier and pump functions of this layer that maintain corneal deturgesence. A large number of corneal endothelial dystrophies feature irregularities in Descemet's membrane, suggesting that cells create and respond to the biophysical signals offered by their underlying matrix. This review provides an overview of the bidirectional relationship between Descemet's membrane and the corneal endothelium. Several experimental methods have characterized a richly topographic and compliant biophysical microenvironment presented by the posterior surface of Descemet's membrane, as well as the ultrastructure and composition of the membrane as it builds during a lifetime. We highlight the signaling pathways involved in the mechanotransduction of biophysical cues that influence cell behavior. We present the specific example of Fuchs' corneal endothelial dystrophy as a condition in which a dysregulated Descemet's membrane may influence the progression of disease. Finally, we discuss some disease models and regenerative strategies that may facilitate improved treatments for corneal dystrophies. Highlights: Descemet's membrane presents biophysical cues to endothelial cells. Mechanotransduction influences cell behavior such as matrix production. In dynamic reciprocity, biophysical cues and matrix production modulate each other. Understanding these relationships helps develop models for corneal dystrophies.